Karakteristik Kimia Ekstrak Rumput Laut Serta Kemampuannya Menghambat Bakteri Salmonella sp. (CHEMICAL CHARACTERISTICS OF ALGAE EXTRACT AND ITS ABILITY TO INHIBIT SALMONELLA SP.) - Kereh, Veybe Gresje; Kusnandar, Feri; Wibawan, I Wayan Teguh; Nahrowi, Nahrowi (Jurnal Veteriner, 2019)
The objectives of this study were to characterize the chemical properties and determine the antibacterial activity of S. crassifolium against Salmonella sp. The algae was extracted using water and ethanol. The results showed that the yield of E. spinosum extract using water solvent showed the highest value (6.53%), followed by S. polycystum extract (3.27%) and S. crassifolium (2.34%). The highest concentration of uronic acid was shown in S. crasifolium extraction (0.90%) using water solvent and the lowest in E. spinosum (0.04%) using ethanol solvent. Inhibitory test against Salmonella sp using 10% S. crassifolium extract showed higher value than using 2.5; 5.0 and 7.5% S. crassifolium extract. It is concluded that the extract of S. crasifolium contain 0.90 % uronic acid with pH= 8 of  that capable of inhibiting the growth of Salmonella sp.